Pengaruh Pemberian Upah Dan Masa Kerja Terhadap Peningkatan Produktivitas Karyawan Pada PT Batik Danar Hadi - Saputro, Dony Catur, Drs. Moech. Nasir, MM (2016)
This study aims to examine and analyze the influence remuneration and tenure to increased employee productivity PT. Batik Danar Hadi. Data collected through the deployment questionnaires and conducted on 88 employees of PT. Batik Danar Hadi. Analysis Data in this study using SPSS. After reviewing the literature and formulation of hypotheses, data collected through questionnaires in 88 employees of PT. Batik Danar Hadi obtained using random sampling techniques. Then do the data analysis obtained using multiple linear regression analysis. this analysis includes the validity and reliability, the classic assumption test, linear regression analysis multiple, hypothesis testing through t test and F, and coefficient analysis determination (R2). From the analysis obtained by regression analysis: Y= 5,342+ 0, 409X_1 + 0,318 X_2 + e Where the variable Productivity (Y), the provision of Wages (X1) and tenure (X2) were tested using the t test showed that both independent variables significantly affect produksitivitas as the dependent variable. Then through the F test shows that the variable pay and tenure the right to test the productivity variables. Figures Adjusted R Square of 0.344 This means that 34.4% of the change / variation Y (Productivity) due to the changes / variations of variable X (Wages and Work Period) while the remaining 65.6% due to changes in other variables not included in the model, for example wages, working environment and so forth.